Tabarru’ underwriting funds: Assessing the influence of investment income and insurance premiums on sharia insurance performance in Indonesia - Nasution, Nursanita; Nurhali, Alfi; Faruqi, Faris (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2023)
This study analyzes the impact of investment and premium income on the Tabarru underwriting funds of Islamic insurance in Indonesia from 2015 to 2018. It employs a quantitative approach, utilizing descriptive statistical methods with Eviews software. The research focuses on Sharia insurance companies registered with the Financial Services Authority (OJK) during this period. The study analyzed data from 19 Islamic insurance companies, focusing on the impact of investment and premium income on Tabarru underwriting funds. The main findings are as follows: First, investment income significantly positively affects the Tabarru funds. Secondly, premium income does not have a significant impact, indicating that premiums align with the level of risk. Public interest statement The findings indicate that Islamic insurance companies in Indonesia should prioritize optimizing their investment strategies to increase their Tabarru underwriting funds. By enhancing investment returns, these companies can reinforce their financial stability and offer improved ser